1998
DOI: 10.1038/bjc.1998.685
|View full text |Cite
|
Sign up to set email alerts
|

Expression in human prostate of drug- and carcinogen-metabolizing enzymes: association with prostate cancer risk

Abstract: Summary The role of two common polymorphisms of enzymes involved in the metabolism of drugs and carcinogens was studied in relation to prostate cancer. The gene encoding one of these enzymes (NAT2) is located in an area where frequent allelic loss occurs in prostate cancer. Mutations at the genes CYP2D6 and NAT2 were analysed by allele-specific polymerase chain reaction and restriction mapping in DNA from 94 subjects with prostate cancer and 160 male healthy control subjects. Eleven prostate specimens were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 33 publications
5
43
1
Order By: Relevance
“…CYP2C9 messenger RNA (mRNA) was detected in the prostate, but mRNA for CYP2C8, CYP2C18, and CYP2C19 were absent (Klose et al, 1999). In contrast to the report of Yokose et al, CYP3A5 has been detected in the prostate (Agundez et al, 1998;Yamakoshi et al, 1999;Finnström et al, 2001). CYP1A, CYP2C, CYP2D, and CYP3A are important catalysts of drug biotransformation.…”
Section: Phase I Drug-metabolizing Enzymes In the Prostatecontrasting
confidence: 50%
See 2 more Smart Citations
“…CYP2C9 messenger RNA (mRNA) was detected in the prostate, but mRNA for CYP2C8, CYP2C18, and CYP2C19 were absent (Klose et al, 1999). In contrast to the report of Yokose et al, CYP3A5 has been detected in the prostate (Agundez et al, 1998;Yamakoshi et al, 1999;Finnström et al, 2001). CYP1A, CYP2C, CYP2D, and CYP3A are important catalysts of drug biotransformation.…”
Section: Phase I Drug-metabolizing Enzymes In the Prostatecontrasting
confidence: 50%
“…The polymorphically distributed CYP2D6 has also been detected in the prostate (Agundez et al, 1998). Activity (N-demethylation of dextromethorphan) was approximately 10% of that in liver.…”
Section: Phase I Drug-metabolizing Enzymes In the Prostatementioning
confidence: 88%
See 1 more Smart Citation
“…Human prostate epithelial cells express NATs and they are capable of activating heterocyclic amines. 16,17 It has been reported that there is an association between NAT genotypes and PCa. [18][19][20] We have reported an association of NAT genotypes with PCa in patients who also have bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…According to the inclusion criteria, 43 studies (Agúndez et al, 1994;Wundrack et al, 1994;Agúndez et al, 1996;Ladona et al1996;Legrand et al, 1996;London et al, 1997;Agúndez et al, 1998;Febbo et al, 1998; González et al, 1998; Hu et Shaw et al, 1998;Krajinovic et al, 1999;Lemos et al, 1999;Topić et al, 2000;Butler et al, 2001;Liu et al, 2002;Sobti et al, 2003;Chen et al, 2004;Fukatsu et al, 2004;Li et al, 2004;Gajecka et al, 2005;Gomes et al, 2005;Guo et al, 2005;Liang et al, 2005;Mochizuki et al, 2005;Sobti et al, 2005;Aydin-Sayitoglu et al, 2006;Bonanni et al, 2006;Li et al, 2006;Lemos et al, 2007;Chen et al, 2008;Khedhaier et al, 2008;Majumdar et al, 2008;Ouerhani et al, 2008 ;Torresan et al, 2008;Yan et al, 2008;Altayli et al, 2009;Gutman et al, 2009;Lim et al, 2011;Luo et al, 2011;Zhou et al, 2011) appeared to have met the inclusion criteria and were subjected to further examination. The flow chart of study selection is shown...…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%